2007
DOI: 10.14712/18059694.2017.77
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nasal Pathologies on Obstructive Sleep Apnea

Abstract: Many abnormalities of the nose and pharynx can cause or aggravate snoring and sleep apnea. Nasal septal deviation, nasal polyps, inferior turbinate hypertrophy and rhinitis can cause nasal airway obstructions. Adenoid hypertrophy, nasopharyngitis and nasopharyngeal tumors can cause nasopharyngeal airway narrowing (6).Epidemiological studies have found relationships between a history of nasal stuffiness and snoring (8) and between measured nasal airflow and a history of snoring (3), but attempts to find a linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Thus surgical procedures to remove these obstructions need to be adapted to the individual pattern and type of airway obstruction (Bhattacharjee et al, 2010; Sher et al, 1996). Obstructions can include macroglossia, adenotonsillar hypertrophy, increased nasal resistance, pharyngeal edema, and craniofacial abnormalities such as micrognathia and retrognathia (Bhattacharjee et al, 2010; Enoz, 2007; Lam et al, 2010; Prabhat et al, 2012; Shott and Cunningham, 1992; Verbraecken and De Backer, 2009; White, 2005; Won et al, 2008). Craniofacial factors are particularly important for pediatric OSA (Gozal, 2000).…”
Section: Airway Obstruction and The Importance Of Hypoglossal Actimentioning
confidence: 99%
“…Thus surgical procedures to remove these obstructions need to be adapted to the individual pattern and type of airway obstruction (Bhattacharjee et al, 2010; Sher et al, 1996). Obstructions can include macroglossia, adenotonsillar hypertrophy, increased nasal resistance, pharyngeal edema, and craniofacial abnormalities such as micrognathia and retrognathia (Bhattacharjee et al, 2010; Enoz, 2007; Lam et al, 2010; Prabhat et al, 2012; Shott and Cunningham, 1992; Verbraecken and De Backer, 2009; White, 2005; Won et al, 2008). Craniofacial factors are particularly important for pediatric OSA (Gozal, 2000).…”
Section: Airway Obstruction and The Importance Of Hypoglossal Actimentioning
confidence: 99%
“…In some cases nasal surgery is reported to increase the number of apnea and hypopneas (3) and to induce central apnoea (4) . There are studies that suggest a connection between nasal patency and OSA (5) , and a study by Lofaso (6) has shown increased nasal resistance in patients with OSA compared to controls. Still, little is known about potential differences in nasal geometry and function between OSA patients and healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…In general, nasal anatomical abnormalities were not considered to have a significant effect on OSA pathophysiology. 22) However, Silvoniemi, et al 23) reported that, severe nasal obstruction due to nasal septal deviation can lead to breathing disturbance during sleep. Furthermore, several studies reported that, correction of nasal anatomical deformity such as nasal septal deviation or nasal turbinate hypertrophy might have beneficial effects on sleep quality.…”
Section: Discussionmentioning
confidence: 99%